BIOM-59. TERT PROMOTER MUTATION AND MGMT PROMOTER METHYLATION-MEDIATED SENSITIVITY TO TEMOZOLOMIDE IN IDH-WILDTYPE GLIOBLASTOMA: IS THERE A LINK?. (9th November 2020) - Gramatzki, Dorothee; Felsberg, Jörg; Hentschel, Bettina; Wolter, Marietta; Schackert, Gabriele; Westphal, Manfred; Regli, Luca; Thon, Niklas; Tatagiba, Marcos; Wick, Wolfgang; Schlegel, Uwe; Krex, Dietmar; et al.
Abstract: BACKGROUND: Benefit from temozolomide (TMZ) chemotherapy in the treatment of isocitrate dehydrogenase (IDH)-wildtype glioblastoma is essentially limited to patients with O 6 -methylguanine DNA methyltransferase (MGMT) promoter-methylated tumors. Recent studies suggest that the impact of the MGMT status on chemosensitivity may be modulated by telomerase reverse transcriptase (TERT) promoter hotspot mutations. METHODS: MGMT promoter methylation and TERT promoter mutation status were assessed in an exploratory prospective cohort of IDH-wildtype glioblastoma patients of the German Glioma Network (GGN) (n=298) and validated in a retrospective cohort from Düsseldorf, Germany, and Zurich, Switzerland (n=302). RESULTS: In the prospective GGN discovery cohort of patients with MGMT promoter-unmethylated tumors, TERT promoter mutation showed inferior outcome (p=0.044). In contrast, TERT promoter mutations were not associated with improved outcome in patients with MGMT promoter-methylated tumors. Different TERT promoter hotspot mutations were not associated with distinct outcomes. The association of TERT promoter mutation in MGMT promoter-unmethylated tumors was not confirmed in the retrospective validation cohort. CONCLUSIONS: Analysis of two independent cohorts of glioblastoma patients, including the prospective GGN cohort, did not confirm previous data suggesting that TERT promoter mutations confer an enhanced benefit from TMZ in patients with MGMT promoter-methylated glioblastoma. Thus, diagnostic testing for TERT promoter mutations may not be required for prediction of TMZ sensitivity in IDH-wildtype glioblastoma patients.